Asterix. The secret of the magic potion [videorecording (DVD)] - Clichy, Louis; Clichy, Louis; Astier, Alexandre, 1975-; Astier, Alexandre, 1975- (Viva Pictures Distribution, Llc, 2025)
Based on the best-selling international comic franchise, Asterix, the village's #1 warrior and dopey sidekick Obelix, embark on a hero's quest across the world to find a young wizard worthy of learning the secret of the magic potion, a formula which has long kept their village safe against the invading army of Romans. With an evil wizard named Demonix seeking to steal the legendary potion recipe and attack from the Roman's imminent, Asterix and Obelix have only one chance to save their village forever.